Análise da ambiência institucional na implantação e operacionalização do PRONAF B, no município de Baturité - Pinheiro, Gláucio de Melo (2009)
This research investigates the existence of an adequate institutional environment for the implementation of financing policies for the family farming sector through an analysis of the integrated initiatives carried out between the Banco do Nordeste do Brasil S/A – BNB and its partners, seeking to consolidate family farming as a source of employment and income through the National Program to Strengthen Family Farming – PRONAF B, in the Municipality of Baturité, Ceará State. The objective is to take care of the most critical situations, presenting proposals that aim at improving such conditions, seeking to achieve expected results. More specifically, the main object is to verify if the necessary initiatives for the families that benefit from the program to improve their social and financial conditions, and especially to increase their family income, are being developed by the Bank and its partners through credit destined to offer better structural conditions to exploit rural activities. Here, we shall focus on the existence of integrated structuring initiatives developed by the institutional organization composed by the Banco do Nordeste, EMATER, the Sindicato Rural (Rural Syndicate) and the Conselho de Desenvolvimento Rural e Prefeitura Municipal (Rural Development Council and the Municipality). This is the most ambitious partnership ever created in the municipality, seeking to improve socioeconomic indicators in the rural community. The work was developed through the case study research methodology, considering individual features. Open interviews with program partners have been carried out, besides the application of closed questionnaires for program beneficiaries and the use of bibliographic research. Results suggest that even with the more availability of funds in recent years and the consequent growth in the number of family farmers included in the program, the good level of satisfaction of program beneficiaries and the obvious improvement in their socioeconomic situation, there are still some obstacles for the improvement of PRONAF B and its necessary upgrading, seeking to widen program goals and objectives. According to program beneficiaries, institutional partners, despite their recognized effort, have yet to develop their attributions in a more coordinated fashion. The PRONAF B, as a public policy, has lead its beneficiaries to have a self-perception never imagined before, however they still feel orphans with regards to the work developed by the institutional partnership as a team. This arrangements, which include the participation of the Banco do Nordeste, must stimulate, and not just through credit, the development of new business opportunities, both agricultural and non-agricultural, for the poorest rural families, considering a more intensive use of production means and particularly the land, also taking into account the peculiarities of each of these families with regards to their vocation, their desires and the location of their residencies and places of work. It is therefore necessary to exercise political pressure on the other institutional partners in order to grant permanent public services for rural citizens, not just to identify them, but rather to offer them knowledge and access to their citizenship rights and obligations. The perception theses citizens have on the results of a public policy like the PRONAF B, is affected by the peculiarities of the rural reality in which they live and the institutional environment conditions in which the program is being developed.